Scoping Review Dampak Flash Sale dan Live Streaming terhadap Perilaku Impulsive Buying pada E-Commerce - Valentina Febri Dzulhiya Sisdi; Audita Nuvriasari; Ardha Fiki Nikmatul Maula; Alimatus Sahrah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article aims to analyze and map previous studies that examine the influence of flash sale and live streaming promotion strategies on impulse buying behavior within e-commerce platforms in Indonesia. This study uses a scoping review approach by analyzing 10 empirical studies published between 2021 and 2026. The analysis shows that flash sales play a significant role in encouraging impulse purchases by creating a sense of urgency and scarcity. Meanwhile, interactivity stimuli from live streaming elevates consumer arousal, thereby increasing impulsive buying tendencies. These findings suggest that combining live streaming with flash sales in contemporary e-commerce ecosystems can mutually enhance each strategy’s effectiveness. This review aims to provide a comprehensive overview of research trends, gaps in existing literature, and potential directions for future studies. The mapped findings are intended to serve as a reference for e-commerce practitioners in developing more effective and sustainable marketing strategies aligned with consumer behavior.